Functional Analysis of O-GlcNAcylation in Cancer Metastasis - Wu, Donglu; Jin, Jingji; Qiu, Zhidong; Liu, Da; Luo, Haoming (Frontiers in Oncology, 2020)
One common and reversible type of post-translational modification (PTM) is the addition of O-linked β-N-acetylglucosamine (O-GlcNAc) modification (O-GlcNAcylation), and its dynamic balance is controlled by O-GlcNAc transferase (OGT) and glycoside hydrolase O-GlcNAcase (OGA) through the addition or removal of O-GlcNAc groups. A large amount of research data confirms that proteins regulated by O-GlcNAcylation play a pivotal role in cells. In particularly, imbalanced levels of OGT and O-GlcNAcylation have been found in various types of cancers. Recently, increasing evidence shows that imbalanced O-GlcNAcylation directly or indirectly impacts the process of cancer metastasis. This review summarizes the current understanding of the influence of O-GlcNAc-proteins on the regulation of cancer metastasis. It will provide a theoretical basis to further elucidate of the molecular mechanisms underlying cancer emergence and progression.